Escaping the Red Queen: Health as a corporate food marketing strategy. (December 2021) - Cuevas, Soledad; Patel, Nishali; Thompson, Claire; Petticrew, Mark; Cummins, Steven; Smith, Richard; Cornelsen, Laura
Abstract: Public health advocates highlight the role of corporate actors and food marketing in shaping diets and health. This study analyses insider-oriented communications in food industry magazines in the UK to analyse actions and narratives related to health and nutrition, providing insights into relatively overlooked areas of marketing strategy including inter-firm dynamics. From a sample of four specialized food industry magazines covering the main industry segments we identified 319 articles (published 2007–2018) mentioning health or nutrition together with industry actions affecting the food environment. We identified health-related actions and analysed underlying strategies through content and thematic analyses. Health and nutrition have a rapidly growing role in food marketing strategy. Content analysis revealed a focus on ultra-processed foods, as well as product and nutrient-specific trends including increased health-based marketing of snacks and "protein rich" products. Health-related actions predominantly relied on consumer agency rather than invoking structural food environment changes. Thematic analysis identified proactive and defensive marketing strategies. Proactive approaches included large investments in health-related promotion of ultra-processed foods which are made highly visible to competitors, and the reliance on a "credence goods" differentiation strategies. Defensive strategies included a 'Red Queen' effect, whereby firms take health-related actions to keep up with competitors. These competitive strategies can create challenges, as well as some opportunities, for public health promotion. Challenges can include undermining efforts to support product comparison and healthier choice, and limiting firms' engagement in specific health improving actions. Systematic analysis of health-oriented marketing strategies could support more effective public health intervention. Highlights: We analyse a decade of insider-oriented news from UK food industry magazines. We focus on health-related food marketing strategy and public health implications. Important drivers include policy, consumer awareness and inter-firm dynamics. There is potential for misalignment between key strategies and public health goals. Marketing strategy and inter-firm dynamics monitoring can support effective policy.